Zirconia Crowns as an Advanced Solution for Pediatric Dental Caries: A Comprehensive Review of Biochemical Considerations and Management Approaches - Alnaji, Ibrahim Ahmed Jaber; Zeila, Latifa Bakri Yusuf; Alnami, Naima Hussain Mohammed; Alkhaldi, Amal Sulaiman Muteb; Sheik, Rasha Yahya; Debaji, Halimah Mousa; Ahmad, Salma Ismail; Alanazi , Ashwaq Awad; Alwabari, Israa Mohammed Hussain (Journal of Ecohumanism, 2024)
Background: Pediatric dental caries is a prevalent issue, necessitating effective restorative solutions. Zirconia crowns have emerged as a promising option due to their superior mechanical properties and aesthetics compared to traditional materials. Understanding the biochemical considerations and management approaches associated with zirconia crowns is essential for optimizing their use in pediatric dentistry. Methods: This comprehensive review analyzes recent literature on zirconia crowns, focusing on their composition, mechanical properties, translucency, preparation techniques, and bonding characteristics. A systematic search was conducted across databases such as PubMed, Scopus, and Embase, retrieving studies from 2000 to 2023 that detail advancements in zirconia materials and their clinical applications. Results: The review highlights that monolithic zirconia crowns offer exceptional strength, aesthetics, and biocompatibility, making them suitable for pediatric patients. Advances in zirconia formulations have enhanced translucency and reduced the need for extensive tooth reduction. However, challenges remain in achieving optimal bonding strength due to zirconia’s low surface energy. Surface treatments and the use of adhesive cements containing phosphate monomers have shown promise in improving adhesion. Conclusion: Zirconia crowns represent a significant advancement in pediatric restorative dentistry, combining durability and aesthetic appeal. Ongoing research is needed to refine bonding techniques and improve clinical outcomes. The integration of zirconia crowns into pediatric dental practice requires a thorough understanding of their properties and the implementation of effective management strategies